2000
DOI: 10.1352/0895-8017(2000)105<0431:pcateo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Personal Control and the Ecology of Community Living Settings: Beyond Living-Unit Size and Type

Abstract: Personal control exercised by 74 adults from community living settings in Minnesota was evaluated. Comparisons between living-unit sizes or types controlled statistically for pre-existing differences in adaptive and challenging behavior. Individuals living semi-independently exercised more personal control than did residents of HCBS Waiver-funded settings, who had more personal control than persons from community ICFs/MR. Within the 1- to 5-person size range, size-related differences were detected in personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 0 publications
10
95
1
7
Order By: Relevance
“…While some of these obstacles are the result of informal routines and cultures of working in particular sites (Harris, 2003;Rawlings, Dowse & Promoting choice and control.. Shaddock, 1995), others are due to regulatory frameworks, local organisational policy, resources and the existing structure of services (Bannerman et al, 1990;Dowson, 1997;Stancliffe et al, 2000). In both cases, staff are held accountable; in the first case to fellow workers, in the second to management.…”
Section: ) Conflicting Agendas and Inspection Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of these obstacles are the result of informal routines and cultures of working in particular sites (Harris, 2003;Rawlings, Dowse & Promoting choice and control.. Shaddock, 1995), others are due to regulatory frameworks, local organisational policy, resources and the existing structure of services (Bannerman et al, 1990;Dowson, 1997;Stancliffe et al, 2000). In both cases, staff are held accountable; in the first case to fellow workers, in the second to management.…”
Section: ) Conflicting Agendas and Inspection Regimesmentioning
confidence: 99%
“…Clearly these requirements put obstacles in the way of the residents' independence which none of us face in our own homes. By complying with relevant regulations and procedures, the staff are compelled to follow procedures and practices that actively disempower the users of that service (for another example see Stancliffe et al, 2000).…”
Section: ) Conflicting Agendas and Inspection Regimesmentioning
confidence: 99%
“…Research has demonstrated that while youth and adults with disabilities have the capacity to be selfdetermined, they are generally less self-determined than their peers without disabilities (Stancliffe, Abery & Smith, 2000;Wehmeyer, Kelchner & Richards, 1996). When provided self-determination instruction people with disabilities are more self-determined (Wehmeyer, Palmer, Lee et al, 2011) and have higher rates of successful postsecondary (Morningstar, Frey, Noonan et al, 2010) and employment outcomes including higher wages and increased likelihood of receiving benefits such as vacation, sick leave and health care (Wehmeyer & Bolding, 1999;Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997).…”
Section: Self-determination Training and Practicementioning
confidence: 99%
“…Concretamente, la literatura científica actual se refiere a la repercusión de variables como la inteligencia, la edad, el género, las habilidades sociales y la conducta adaptativa o los valores, creencias y actitudes de la persona sobre la promoción de la autodeterminación en la persona (véase Tabla 1). Del mismo modo, algunas investigaciones han prestado especial atención al influjo del ambiente global y próximo que rodea a la persona sobre la consecución de una conducta autodeterminada (Stancliffe, Abery y Smith, 2000;Wehmeyer, Abery, Mithaug y Stancliffe., 2003).…”
Section: Introductionunclassified